Capturing and releasing of hepatocellular carcinoma EpCAM+ and EpCAM- circulating tumor cells based on photosensitive intelligent nanoreactor - Mao, Zhifang; Hu, Meng; Shen, Qinglin (Frontiers in Bioengineering and Biotechnology, 2024)
Epithelial cell adhesion molecule negative circulating tumor cells (EpCAM-CTCs) and EpCAM positive CTCs (EpCAM+ CTCs) have different biological characteristics. Therefore, the isolation of EpCAM+ CTCs and EpCAM-CTCs is a new strategy to study the heterogeneity of tumor cells. The azobenzene group (Azo) and cyclodextrin (CD) composite system forms a photosensitive molecular switch based on the effect of external light stimulation. We used the technology of specifically capturing CTCs using anti-EpCAM and aptamers functionalized nanochips. Both anti-EpCAM and aptamers can be connected to Azo through the 1-ethyl-3-(3dimethylaminopropyl) carbodiimide/N-hydroxysuccinimide (EDC/NHS) modification process. Therefore, we assume that a photosensitive intelligent nanoreactor(PSINR) modified with anti-EpCAM can be used to capture EpCAM+ CTCs; Utilizing the characteristics of aptamer and ligand binding, a PSINR modified with aptamer is used to capture EpCAM-CTCs; Then, two PSINRs were separated and stimulated with light to release EpCAM+ CTCs and EpCAM-CTCs, respectively. Based on the isolation the EpCAM+ CTCs and EpCAM-CTCs, we expected to reveal the key biological mechanisms of tumor recurrence, metastasis and drug resistance, and make the individualized treatment of liver cancer more targeted, safe and effective, and provide a new basis for the final realization of accurate and individualized treatment of tumors.